2020
DOI: 10.5194/essd-2020-300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

OceanSODA-ETHZ: A global gridded data set of the surface ocean carbonate system for seasonal to decadal studies of ocean acidification

Abstract: Abstract. Ocean acidification has altered the ocean's carbonate chemistry profoundly since preindustrial times, with potentially serious consequences for marine life. Yet, no long-term global observation-based data set exists that permits to study changes in ocean acidification for all carbonate system parameters over the last few decades. Here, we fill this gap and present a methodologically consistent global data set of all relevant surface ocean parameters, i.e., dissolved inorganic carbon (DIC), total alka… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 61 publications
3
47
1
Order By: Relevance
“…Further, numerical modeling study focusing on the coastal upwelling region of California Current System has also reported a similar pH range (7.85-8.20) (Hauri et al, 2013). Model derived pH records available for our study region (Gregor & Gruber, 2021) (Figure 5b) and for the north-western Arabian Sea (Sreeush et al, 2019) are characterized by long-term declining trend with much smaller pH variability. Whereas our δ 11 B coral derived pH record shows much larger pH variability with no discernable decreasing trend (Figure 5a) highlighting divergence between the proxy based reconstruction and numerical model simulations of the past pH.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Further, numerical modeling study focusing on the coastal upwelling region of California Current System has also reported a similar pH range (7.85-8.20) (Hauri et al, 2013). Model derived pH records available for our study region (Gregor & Gruber, 2021) (Figure 5b) and for the north-western Arabian Sea (Sreeush et al, 2019) are characterized by long-term declining trend with much smaller pH variability. Whereas our δ 11 B coral derived pH record shows much larger pH variability with no discernable decreasing trend (Figure 5a) highlighting divergence between the proxy based reconstruction and numerical model simulations of the past pH.…”
Section: Resultssupporting
confidence: 74%
“…This short and discrete record of BOBOA is insufficient to quantify OA rates and to decipher any long-term OA trend in the Indian Ocean. The lack of instrumental and proxy based pH data leads to a dependency on calculation or model-based estimation of pH change for this region (Gregor & Gruber, 2021;Jiang et al, 2019;Joshi et al, 2020;Sreeush et al, 2019;Valsala et al, 2021;Xue et al, 2014). Thus, the regional and global scale forcing factors that can potentially influence the amplitude and frequency of pH changes in the Indian Ocean need to be recognized and to quantify their relative roles.…”
mentioning
confidence: 99%
“…The CanESM5 control ensemble is capable of capturing the phasing and magnitude in the climatological seasonal cycle of ΔpCO 2 as measured at the Woods Hole Oceanographic Institution Hawaii Ocean Timeseries Site (WHOTS) buoy, though the spring minimum is deeper in approximately half of the CanESM ensemble members than observed ( Figure S1b). While the annual mean surface ocean pH over 2015-2018 exhibits similar spatial patterns between modeled pH and an observation-based product (Gregor & Gruber, 2020), the modeled pH is generally lower than that from observation-based estimates ( Figure S2). As with ΔpCO 2 , a lack of observation-based climatological estimates of pH in the seasonally ice covered Southern Ocean and Arctic precludes investigation of model-observation similarity in these regions.…”
Section: 1029/2020gl092263mentioning
confidence: 74%
“…Software for the GRaCER framework is available on Zenodo https://doi.org/10.5281/zenodo.4455354 (Gregor, 2021). The OceanSODA-ETHZ data set is available at https://doi.org/10.25921/m5wx-ja34 (Gregor and Gruber, 2020).…”
Section: Code and Data Availabilitymentioning
confidence: 99%